Haematopoietic cell transplantation with and without sorafenib maintenance for patients with FLT3‐ITD acute myeloid leukaemia in first complete remission. (19th July 2016) - Brunner, Andrew M.; Li, Shuli; Fathi, Amir T.; Wadleigh, Martha; Ho, Vincent T.; Collier, Kerry; Connolly, Christine; Ballen, Karen K.; Cutler, Corey S.; Dey, Bimalangshu R.; El‐Jawahri, Areej; Nikiforow, Sarah; et al.
Summary: We performed a retrospective study analysing the effect of sorafenib, an oral fms‐Like Tyrosine Kinase 3 (FLT3)/multikinase inhibitor, as post‐transplant maintenance in adult patients with FLT3 ‐internal tandem duplication (ITD) acute myeloid leukaemia (AML). We identified consecutive patients with FLT3‐ ITD AML diagnosed between 2008 and 2014 who received haematopoietic cell transplantation (HCT) in first complete remission (CR1). Post‐HCT initiation of sorafenib (yes/no) was evaluated as a time‐varying covariate in the overall survival/progression‐free survival (OS/PFS) analysis and we performed a landmark analysis of controls alive without relapse at the median date of sorafenib initiation. We identified 26 sorafenib patients and 55 controls. Median follow‐up was 27·2 months post‐HCT for sorafenib survivors, and 38·4 months for controls ( P  = 0·021). The median time to initiating sorafenib was 68 days post‐HCT; 43 controls were alive without relapse at this cut‐off. Sorafenib patients had improved 2‐year OS in the d+68 landmark analysis (81% vs. 62%, P  = 0·029). Sorafenib was associated with improved 2‐year PFS (82% vs. 53%, P  = 0·0081) and lower 2‐year cumulative incidence of relapse (8·2% vs. 37·7%, P  = 0·0077). In multivariate analysis, sorafenib significantly improved OS [Hazard ratio (HR) 0·26, P  = 0·021] and PFS (HR 0·25, P  = 0·016). There was no difference in 2‐year non‐relapse mortality (9·8% vs. 9·3%, P  = 0·82) or 1‐year chronic graft‐versus‐host disease (55·5% vs. 37·2%, P  = 0·28). These findings suggest potential benefit of post‐HCT sorafenib in FLT3 ‐ITD AML, and support further evaluation of post‐HCT FLT3 inhibition.